View factors of spherical, conic, and cylindrical spiral surfaces. (November 2021) - Lebedev, Vladimir A.; Solovjov, Vladimir P.; Webb, Brent W.
Highlights: View factors associated with spherical, conic, and cylindrical surfaces are presented. Spherical surfaces studied are defined using parametric equations, and their areas are found using differential geometry methods. Abstract: The view factors of a family of spiral surfaces of different type are derived using parameterization and differential geometry methods. Analytical results are presented for the view factors of the conic, spherical and cylindrical spiral surfaces.